2018
DOI: 10.1038/s41427-018-0071-0
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular hydrogels cross-linked by preassembled host–guest PEG cross-linkers resist excessive, ultrafast, and non-resting cyclic compression

Abstract: Poly(ethylene glycol) (PEG)-based hydrogels are promising materials for biomedical applications because of their excellent hydrophilicity and biocompatibility. However, conventional chemically cross-linked PEG hydrogels are brittle under mechanical loading. The mechanical resilience and rapid recovery abilities of hydrogel implants are critical in load-bearing tissues, such as articular cartilage, which are routinely subjected to cyclic loadings of high magnitude and frequency. Here, we report the fabrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…The mechanical resilience and rapid recovery abilities of hydrogel implants are critical in load-bearing tissues, such as articular cartilage, which are routinely subjected to cyclic loadings of high magnitude and frequency 211 , 212 . Fortunately, it has been proven that the energy dissipation by the hydrogels can protect the loaded cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical resilience and rapid recovery abilities of hydrogel implants are critical in load-bearing tissues, such as articular cartilage, which are routinely subjected to cyclic loadings of high magnitude and frequency 211 , 212 . Fortunately, it has been proven that the energy dissipation by the hydrogels can protect the loaded cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, dynamic single-chain nanogels as building blocks provide effective energy dissipation to bulk hydrogels, thereby protecting the encapsulated stem cells from deleterious mechanical shocks in a 3D matrix 211 . Additionally, PEG-adamantane supramolecular hydrogels exhibit substantial deformability and excellent capacity to dissipate massive amounts of loading energy and have a rapid, full recovery during excessive, ultrafast, and nonresting cyclic compression 212 .…”
Section: Discussionmentioning
confidence: 99%
“…[57] Another method of generating injectable, physically crosslinking hydrogels is through using host-guest chemistry. [58][59][60][61][62][63][64][65] The most common types of host molecules are cyclodextrin (CD), cucurbituril (CB), and crown ether (CE). They can couple with linear polymers or small guest molecules that are able to fit into the cavity of the host molecules.…”
Section: Physically Crosslinked Injectable Hydrogelsmentioning
confidence: 99%
“…The prepared hydrogel showed enhanced mechanical properties such as substantial deformability, excellent stability to the applied stress, and an ultrafast and nonresting cyclic compression. [62] Feng et al reported injectable gelatin hydrogels physically crosslinked by host-guest complexations that were further reinforced by limited chemical crosslinking (Figure 2). In this respect, photo-crosslinkable acryloyl -cyclodextrin (Ac--CD) was synthesized and physically crosslinked with the aromatic residues of gelatin (e.g., phenylalanine, tyrosine, and tryptophan) via host-guest interactions.…”
Section: Physically Crosslinked Injectable Hydrogelsmentioning
confidence: 99%
“…To synthesize adamantane-capped PEG (Ad-PEG5000-Mal), a 1:1 (w/w) ratio of adamantane carbonyl chloride and maleimide-PEG5000-hydroxyl was dissolved in anhydrous chloroform (5 mL chloroform per 1 g mixture), according to a previous protocol 28 . Equal molar amounts of triethylamine to PEG was then added dropwise and the solution was allowed to react for 24 hrs.…”
Section: Protein-peg-adamantane Conjugation Synthesismentioning
confidence: 99%